To find the solution to both equations, we can substitute the value of Y from the second equation into the first equation.
From the second equation, Y = X + 5
Substitute Y = X + 5 into the first equation 4X + 3(X + 5) = 15
Simplify the equation: 4X + 3X + 15 = 15
7X + 15 = 15
7X = 0
X = 0
Now that we have found the value of X, we can substitute it back into the second equation to find the value of Y.
Y = X + 5
Y = 0 + 5
Y = 5
Therefore, the solution to the system of linear equations is X = 0 and Y = 5.
YX plus 3Y equals 15 Y equals X +5
Review the graph of a system of two linear equations into variables 4X plus 3Y equals 15 and Y equals X +5 find the solution to both equations
1 answer